An Eccentric Presentation of Chondroblastoma of the Temporomandibular Joint: A Case Report - Ronald Anto; Suresh Mani (ENT Updates, 2024)
Chondroblastoma, a rare tumor, can affect the temporomandibular joint (TMJ) and cause symptoms similar to those of other TMJ problems. Although benign, it has aggressive traits such as bone invasion. A 45-year-old man reported swelling in the left preauricular region for two years. On examination, it was bony hard, not tender, and did not move when the mouth was opened. We diagnosed the patient with pigmented villonodular synovitis based on the radiographic findings. After excision, the histopathological report suggested an uncommon chondroblastoma pathology. Osteolytic tumors of the bone are difficult to diagnose preoperatively owing to their nonspecific clinical and radiographic characteristics. When an osteolytic bony lesion of the temporal bone is present, chondroblastoma should be considered a differential diagnosis.